The morphology and incidence of the accessory foramen transversarium in human dried cervical vertebrae as well as their clinical significance in the Eastern Indian population - Rakesh Ranjan; Md. Zahid Hussain; Soni Kumari; Vijay Kumar Singh; Rashmi Prasad (Asian Journal of Medical Sciences, 2022)
Background: A characteristic feature of the cervical vertebrae (C1–C7) is the presence of a foramen tranversarium on the transverse process. The cervical vertebrae are the smallest in size as compared to the thoracic and lumbar vertebrae and are characterized by a foramen in each transverse process, which is not found in any other vertebra. Except for the seventh cervical vertebra, which transmits only the vertebral vein, this foramen transmits the vertebral artery, vein, and sympathetic nerves (a branch from the cervicothoracic ganglion) in all cervical vertebrae. Any deviation in the development of the foramen transversarium (FT) causes changes in the course, relationships, and structure (stenosis and lumen narrowing) of the vertebral artery and its associated structures. Aims and Objectives: The aims of this study were to establish the location, shape, size, and incidence of accessory FT in dry human cervical vertebrae of Eastern Indian population. Materials and Methods: An observational cross-sectional study was conducted on 170 dry cervical vertebrae (Typical-123 and Atypical-47) of unknown sex and age after getting approval from the Institutional Ethics Committee. Range, frequencies, percentage, mean, standard deviation, and P value were calculated. P<0.05 was taken as significant. Results: The foramen tranversarium in the transverse process is present in all 170 cervical vertebrae examined. Of the 170 cervical vertebrae, the accessory FT is found in 24 (14.12%) of the vertebrae. In both typical and atypical cervical vertebrae, the accessory FT is more common on the right side. On the axis vertebra, no accessory FT was found. Conclusion: Understanding the accessary FT and the considerable variation in different cervical vertebrae (C1-C7) in terms of their size, shape, and number of FT are essential for routine spine surgical procedures in the cervical region to avoid post-operative complications. This study is also important for the teaching and acknowledgement of undergraduate and postgraduate students in anatomy as well as in orthopedics, neurosurgery, and radiology departments.